Potensi Pengembangan Pariwisata Syariah Nepal Van Java Melalui Analisis Swot Di Dusun Butuh Kaliangkrik Magelang - Siti Maratus Sakdiyah; M. Pudail; Yeny Fitriyani (Jurnal Mirai Management, 2023)
The purpose of this study is to complete the literature on the Nepal Van Java tourist attraction in Butuh Kaliangkrik Magelang to become sharia-based tourism where previously there has not been much research on SWOT analysis in sharia-based tourism research. In this study using descriptive qualitative methods with SWOT analysis techniques. The subjects in this study were managers, local communities, and tourists. The results of the study using the SWOT analysis technique show that the existence of adequate worship facilities, specific halal culinary, and traditional customs, natural beauty that encourages tourists to practice nature pilgrimage makes Nepal Van Java a potential as sharia tourism. Kata Kunci: Sharia Tourism, SWOT analysis, Tradition, Tourists, Halal Food